2022
DOI: 10.1039/d1ta10433k
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of CeO2 particles with aligned grains drives sintering of Pt single atoms in Pt/CeO2 catalysts

Abstract: Understanding the sintering mechanism of platinum-group-metals (PGMs) supported on reducible oxides, such as CeO2, is of fundamental and practical importance for the development of durable catalysts. It has been reported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Our observation that Ce 3+ is preferentially formed at and around the boundary between CeO 2 particles (Figure ) and that both the rate and amount of H 2 consumption on Pt/CeO 2 decrease when the formation of boundaries between CeO 2 particles is suppressed (Figure b and Table S2) support this inference. Recently, we also found that the Pt sintering is promoted when the lattice of neighboring CeO 2 particles are aligned . That is, the boundary between CeO 2 particles not only affects how H 2 reacts with Pt/CeO 2 but also plays an important role in determining the thermal stability of dispersed Pt species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observation that Ce 3+ is preferentially formed at and around the boundary between CeO 2 particles (Figure ) and that both the rate and amount of H 2 consumption on Pt/CeO 2 decrease when the formation of boundaries between CeO 2 particles is suppressed (Figure b and Table S2) support this inference. Recently, we also found that the Pt sintering is promoted when the lattice of neighboring CeO 2 particles are aligned . That is, the boundary between CeO 2 particles not only affects how H 2 reacts with Pt/CeO 2 but also plays an important role in determining the thermal stability of dispersed Pt species.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we also found that the Pt sintering is promoted when the lattice of neighboring CeO 2 particles are aligned. 70 That is, the boundary between CeO 2 particles not only affects how H 2 reacts with Pt/CeO 2 but also plays an important role in determining the thermal stability of dispersed Pt species. Although the boundaries between support particles are often neglected when constructing model structures, a more in-depth consideration of the boundaries between support particles may be important for understanding the properties of powder heterogeneous catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…While STM is well suited for imaging single-crystal surfaces, transmission electron microscopy (TEM) is better matched for imaging nanoscale catalyst particles (e.g., spherical nanoparticles, nanorods, and nanowires). The development of in situ holders for TEM in which gas and liquids can be introduced has enabled atomic-level visualization of the changes in nanoscale catalysts after reactive chemical species (e.g., H 2 , O 2 , or CO) are introduced into the cell. In-situ holders designed for introducing gases are particularly useful for studying structural changes at elevated temperatures (e.g., 150 to 800 °C) during vapor-phase reactions such as methane oxidation, CO oxidation, and other reactions. , In-situ liquid-cell holders with the ability to apply an electrical bias can be used to monitor morphological changes during electrochemical processes such as lithiation/delithiation, metal dendrite formation, and, more recently, electrochemical reactions including water oxidation and oxygen reduction. , Changes in the surface structure of photocatalyst particles, such as titanium dioxide (TiO 2 ), under UV irradiation and in the presence of H 2 O have also been imaged. , While transmission electron microscopes can be coupled with instrumentation for detecting reaction products through mass spectrometry (MS) or electron energy loss spectroscopy (EELS), ,, there is currently no way to correlate a specific region of the catalyst with the number of turnovers at that site nor how the observed structural changes affect its relative activity. So far, mapping the relative reactivity of different regions has been limited to reactions that produce gaseous products (e.g., water splitting to produce H 2 and O 2 gas) by imaging the formation of gas bubbles in liquid cells. ,, However, the gas bubbles are significantly larger (i.e., tens to hundreds of nanometers) than the reaction sites producing the bubbles.…”
Section: A Comparison Of Techniques For In Situ Imaging Of Heterogene...mentioning
confidence: 99%
“… 125 129 In-situ holders designed for introducing gases are particularly useful for studying structural changes at elevated temperatures (e.g., 150 to 800 °C) during vapor-phase reactions such as methane oxidation, 130 CO oxidation, 131 133 and other reactions. 134 , 135 In-situ liquid-cell holders with the ability to apply an electrical bias can be used to monitor morphological changes during electrochemical processes such as lithiation/delithiation, metal dendrite formation, 136 139 and, more recently, electrochemical reactions including water oxidation and oxygen reduction. 140 , 141 Changes in the surface structure of photocatalyst particles, such as titanium dioxide (TiO 2 ), under UV irradiation and in the presence of H 2 O have also been imaged.…”
Section: A Comparison Of Techniques For In Situ Imaging Of Heterogene...mentioning
confidence: 99%
“…Datye et al developed defect-stabilized Pt-on-CeO 2 SACs in oxidizing environments using atom trapping . However, various aggregation behaviors of Pt single atoms were observed under operating conditions. Therefore, opinions vary when it comes to the geometric and electronic structures of active sites on SACs in different reactions. For example, monatomic Rh sites were considered the true active center in CO 2 hydrogenation, while the combination of Rh 1 and Rh 3 sites was reported to play an important role in the initial CO activation and the subsequent C–C coupling/C 2 hydrogenation in CO hydrogenation .…”
Section: Introductionmentioning
confidence: 99%